The cultural production of an 'employable person': A case of madrasa students in West Bengal, India. Issue 3 (3rd July 2018) - Jaju, Garima
Abstract : Madrasas are increasingly being reformed across South Asia with the intended aim of 'social change' through mainstreaming its marginalized Muslim population. While the transformative change, as promised in policy and popular discourse, remains distant, a vernacular cultural variant of this 'change' is intimately felt in the changing subjectivities of the students. As future holders of degrees now recognized by the government, the students imagine themselves as 'employable persons'. In so doing, they challenge their long drawn marginal position in the economy and society as 'unemployable persons'. By separating 'being employable' from being employed, the students are social agents innovatively responding to the broader socio-cultural and political economy, to achieve an elevated status for themselves, despite their likely unemployment and continued socio-economic marginality. While the madrasa students fail in accessing social mobility, they reproduce their condition in an agentive manner – through contestation and 'partial penetration'.